Indonesian Language Teachers' Perceptions of ChatGPT Use in Writing Instruction in the Digital Literacy Era - Hanis Nurwidati; Farida Nugrahani; Agata Margareti; Prih Haryati; Tubandi; Anom Wija Pratama (PT FORMOSA CENDEKIA GLOBAL, 2026)
The emergence of generative artificial intelligence, particularly ChatGPT, has created both opportunities and challenges for writing instruction in secondary education. This study aims to: (1) describe Indonesian Language teachers’ understanding of ChatGPT as a tool for writing instruction; (2) analyze teachers’ perceptions of the Use of ChatGPT in writing instruction; and (3) explore strategies for the responsible use of ChatGPT to support students’ writing skills and digital literacy. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews with three Indonesian Language teachers, classroom observations, and analysis of instructional documents. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that teachers possess a functionally pragmatic understanding of ChatGPT and perceive it as a learning support tool that facilitates the pre-writing process, particularly in generating ideas, organizing outlines, and providing initial feedback. Teachers’ perceptions of ChatGPT were generally positive due to its potential to improve instructional efficiency; however, concerns remained regarding students’ cognitive dependency, academic integrity, limited digital literacy among teachers, and infrastructural constraints. Teachers developed several responsible-use strategies, including guided prompting, comparative writing, error analysis, and reflective journaling, to ensure that AI supports the development of critical thinking and independent writing skills. The findings contribute to the development of a responsible AI integration model for Indonesian language instruction at the secondary school level.